Biological and thermochemical conversion of human solid waste to soil amendments. (15th April 2019) - Krounbi, Leilah; Enders, Akio; van Es, Harold; Woolf, Dominic; von Herzen, Brian; Lehmann, Johannes
Highlights: Monetary value based on agronomic components was highest with HSW pyrolyzed at 600 °C. HSW pyrolyzed at 700 °C was of greatest monetary value compared to organic amendments. High mass recovery with torrefaction maximizes monetary value per unit weight feedstock. Compost had the lowest value under any scenario. Abstract: Biological and thermochemical sanitization of source-separated human solid waste (HSW) are effective technologies for unsewered communities. While both methods are capable of fecal pathogen sterilization, the agronomically-beneficial properties of waste sanitized between methods remains unclear. Therefore, this study compared recovery and quality of soil amendments produced by compostation, torrefaction, and pyrolysis of HSW, established their financial value, and quantified tradeoffs between product value and conversion efficiency. Temperature and associated mass losses significantly affected the physical and chemical properties of thermochemically-treated HSW. Thermophilic composting, a biological sanitation method practiced in informal settlements in Nairobi, Kenya, produced an amendment that contained between 16 and 858-fold more plant-available nitrogen (N; 214.5 mg N/kg) than HSW pyrolyzed between 300 and 700 °C (0.2–15.2 mg N/kg). Conversely, HSW pyrolyzed at 600 °C had four-fold higher plant-available phosphorus (P; 3117 mg P/kg) and five-fold higher plant-available potassium (K; 7403 mg K/kg) than composted HSW (716 mg P/kg and 1462 mg K/kg). Wide variation between international fertilizer prices on the low end and regional East African prices on the high end resulted in broad-spaced quantiles for the value of agronomic components in HSW amendments. Phosphorus and K comprised a disproportionate amount of the value, 52–87%, compared to plant-available N, which contributed less than 2%. The total value of treated HSW, summed across all agronomic components per unit weight amendment, was greatest for thermochemically-treated HSW at 600 °C, averaging 220 USD/Mg, more than four-fold that of composted HSW, 53 USD/Mg. In contrast, torrefaction provided the highest monetary value per unit weight feedstock, 144 USD/Mg, as low heating temperatures engender minimal mass loss and higher nutrient densities per unit weight feedstock, compared to composted or pyrolyzed HSW. When benchmarked against total N, P, and K of eight commonly-applied organic amendments, including sewage-sludge (Milorganite), compost, and alfalfa meal, HSW pyrolyzed at 700 °C was of greatest value per unit weight of amendment, 365 USD/Mg, compared to 89 USD/Mg for composted HSW, and contained 2.9% total N (0.5 mg available N/kg), 3.1% total P (7640 mg available P/kg), 3.5% total K (17, 671 mg available K/kg).